The Effect of Bot Accounts on Community Toward Online Loans on Twitter - Ahmad Ikhsan; Farrel Arrizal; Angelica Cintya Mannuela Wibowo; Nur Aini Rakhmawati (Sistemasi: Jurnal Sistem Informasi, 2022)
The massive advancement of technology is supported by the convenience and ease of transacting carried by fintech applicators, especially for the online loan (pinjol) experience is getting easier. However, the ease of it raises issues of unrest in the community, many complaints that arise such as unnatural bills, how debt collectors charge at the time of maturity, and the issue of sharing the borrower's personal data to the public. Another concern of the existence of online loans is the clarity of their legality, there are still many online loan applicators that are not registered with the Financial Services Authority (OJK). It leads to a negative attitude. The purpose of this study is to find out public sentiment towards the existence of online loans through social media Twitter. The study also wanted to find out if there were significant sentiment differences when bot accounts were in the dataset. Researchers obtained 941 lines of twitter data by not separating bot accounts. If the bot account is separated, the data becomes 432 data. After a deeper analysis, it was found that the tendency of sentiment towards online loans in the community was negative with a value of 45.6%. After separating the bot account from the dataset, the negative sentiment still dominated from the existing sentiment to 54.2%. So that it can be drawn another conclusion that the existence and absence of bot accounts in the dataset only gives a small influence on other sentiments, bot accounts do not change the initial conclusion that said public sentiment towards the existence of online loans tends to lead to negative attitudes.